Ultrasound-enhanced flow injection chemiluminescence for determination of hydrogen peroxide - Gillian M. Greenway (2018)
A novel ultrasonic flow injection chemiluminescence (FI-CL) manifold for determining hydrogen peroxide (H2O2) has been designed and evaluated. Chemiluminescence obtained from the luminol-H2O2-cobalt(ii) reaction was enhanced by applying 120 W of ultrasound for a period of 4 s to the reaction coil in the FI-CL system and this enhancement was verified by comparison with an identical manifold without ultrasound. The system was developed for determining ultra-trace levels of H2O2and a calibration curve was obtained with a linear portion over the range of 10-200 nmol L-1H2O2(correlation coefficient 0.9945). The detection limit (3σ) and the quantification limit (LOQ) were found to be 1 × 10-9and 3.3 × 10-9mol L-1respectively and the relative standard deviation was 1.37% for 2 × 10-7mol L-1H2O2(n = 10). The method was applied to the determination of trace amounts of H2O2in purified water and natural water samples without any special pre-treatments. © The Royal Society of Chemistry 2006.